2021
DOI: 10.3390/foods10061317
|View full text |Cite
|
Sign up to set email alerts
|

Good Attitudes Are Not Good Enough: An Ethnographical Approach to Investigate Attitude-Behavior Inconsistencies in Sustainable Choice

Abstract: This research explores reasons for the attitude-behavior gap of consumers involved with sustainable food choice. For this purpose, the Food Choice Process Model by was applied. The study follows a qualitative approach. Data were collected through ethnographical fieldwork. Over the course of nine months, researchers repeatedly accompanied six families. Each visit lasted several hours and included multiple in-depth discussions, food shopping observations and participation in everyday food behavior. Findings show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 118 publications
0
15
0
Order By: Relevance
“…Another important finding in our study is that the awareness of CDGs had no significant influence on lowering or increasing relative macronutrient intakes. The underlying reason for the lack of link between CDG knowledge and levels of macronutrient intakes is not yet understood, but it may be potentially explained by previous qualitative research on this issue showing that knowledge itself is not enough to influence food choice [ 26 ]. Some studies demonstrated that food choice can depend on the reliability of public information and a broader environment [ 34 ], suggesting that disseminating CDGs to the public alone would not significantly improve the nutrient status of Chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another important finding in our study is that the awareness of CDGs had no significant influence on lowering or increasing relative macronutrient intakes. The underlying reason for the lack of link between CDG knowledge and levels of macronutrient intakes is not yet understood, but it may be potentially explained by previous qualitative research on this issue showing that knowledge itself is not enough to influence food choice [ 26 ]. Some studies demonstrated that food choice can depend on the reliability of public information and a broader environment [ 34 ], suggesting that disseminating CDGs to the public alone would not significantly improve the nutrient status of Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of priorities of a healthy diet, adults who had a higher priority in a healthy diet were more likely to meet the DRI for macronutrients compared to those who had lower priority in a healthy diet. This could be interpreted by one study that demonstrated that personal evaluation or belief in foods, in our case, the priority given to healthy diet, can influence personal food choice [ 26 ]. Since one’s food attitude and values placed in a healthy diet can be developed over time [ 26 ], it is crucially important to implement dietary education and intervention targeting people of younger age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To better account for the asymmetries in the effect sizes associated with each of the three included outcome measures, future investigations should prioritize using observational methods to track changes in dietary behaviors where possible. In addition to providing more precise approximations of changes in food choice (Webb and Sheeran, 2006;Loy et al, 2016;Meyer and Simons, 2021) and minimizing the risks of bias that stem from the so-called "intention-behavior gap, " collecting observational data has the additional benefit of equipping institutional policymakers and foodservice providers with a practical means of making complementary supply-side changes based on information that is collected at the point of purchase. Furthermore, to allow for a better sense of whether the investigated approaches can lead to lasting changes in behavior, researchers should endeavor to evaluate the effects of these initiatives more frequently and over longer intervals of time.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%